(untitled) (Bangladesh Journal of Animal Science, 2017)
The present study was conducted to investigate the seasonal effect on milk production and milk qualities of crossbred dairy cows at DGDF, Sylhet. For these purposes, the data of milk production and milk samples were collected from bulk milk tank at District Govt. Dairy Farm, Sylhet and their qualities were measured by physico-chemical and microbiological tests. The season has a significant effect (p<0.05) on the milk yield and milk quality. The total milk production was highest during the rainy season 3354.00 kg followed by summer 3116.70 kg while the lowest milk production was obtained in winter 2925.50kg. The chemical composition of milk was the lowest in summer 4.27% fat, 3.20% protein, 4.46% lactose and 8.55% SNF and in rainy 3.96% fat, 3.24% protein, 4.49% lactose and 8.53% SNF respectively and the highest in winter 5.30% fat, 3.18% protein, 4.46% lactose and 8.59% SNF. The season had a significant influence on the density and freezing point of the milk (p<0.05). The temperature of the milk varied widely from one season to another season. The temperature was maximum in rainy season 28.77oC while the minimum was 25.80 oC in the winter season. The salt percentage of the milk varied within a small range from one season to another season. During the winter season the average SPC bacteria count was lower compared with the other season, 38.02 ×105 cfu/ml. The highest value was obtained in rainy season 40.50×105 cfu/ml. Coliform bacteria count was on average 4.5×105 cfu/ml in winter, 4.91×105 cfu/ml in summer and 5.46×105 cfu/ml in rainy season. There was no significant difference compared to the value found during the other season. From this study it was found that season had a significant effect on the milk quantity and quality, except for protein, lactose, SNF, SPC and coliforms count. Bang. J. Anim. Sci. 2016. 45 (3): 52-57